SUPERVISI AKADEMIK SEKOLAH DASAR PADA MASA PANDEMI COVID19: A REVIEW - Desimarnis, Desimarnis; Marsidin, Sufyarma; Rifma, Rifma (Jurnal Dedikasi Pendidikan, 2022)
This study is a review of several articles on primary school academic supervision during the pandemic. This study aims to identify and obtain information related to the educational supervision process faced by school principals during the pandemic. The research was conducted in several articles related to the academic supervision of elementary schools during the pandemic. Based on the study results, it was found that supervision activities played a significant role in improving teacher performance. However, the implementation of academic supervision during the Covid-19 period was generally considered to be still less effective and affected the quality of learning in schools which became less than optimal. This can be overcome if the principal as a supervisor can utilize technology that can facilitate the work of the principal as an academic supervisor.